Sphingosine-1-phosphate is a crucial signal for migration of retina Müller glial cells - Simon, Maria Victoria (2015)
PURPOSE. Migration of M¨uller glial cells is enhanced in proliferative retinopathies, but the mechanisms involved are ill defined. Sphingosine-1-phosphate (S1P) is a bioactive sphingolipid synthesized by sphingosine kinase (SphK), which promotes proliferation, migration, and inflammation, acting as an intracellular mediator and activating a family of membrane receptors (S1PRs). We investigated whether S1P regulated glial migration.METHODS. M¨uller glial cell cultures from rat retinas were supplemented with 5 lM S1P, and migration was evaluated by scratch-wound assays. Cultures were treated with SphK inhibitor 2 (SphKI 2), a SphK1 inhibitor, or with W146 and BML-241, S1P1 and S1P3 antagonists, respectively, to investigate whether M¨uller glial cells synthesized S1P and S1P-activated S1PRs to stimulate migration. The effects of LY294002, U0126, and SB203580, which are phosphatidylinositol-3 kinase (PI3K), extracellular signal regulated kinase/mitogen-activatedprotein kinase (ERK/MAPK), and p38 MAPK inhibitors, respectively, on glial migration were determined.RESULTS. Sphingosine-1-phosphate addition prompted the formation of lamellipodia and enhanced glial migration. SphKI 2 almost completely prevented glial migration in controls; BML-241 inhibited this migration both in controls and in S1P-supplemented cultures, whereas W146 had no significant effect. Pretreatment with LY294002 and U0126 abrogated glial migration; SB203580 decreased it partially, although not significantly.CONCLUSIONS. Our results suggest that M¨uller glial cells synthesize S1P, which signals through S1P3 and the PI3K and ERK/MAPK pathways to induce glial migration. As a whole, our data point to a central role for S1P in controlling glial cell motility. Because deregulation of this process is involved in several retinal pathologies, S1P signaling emerges as a potential tool fortreating these diseases.